A Shallow Angle Short-Axis Out-of-Plane Approach Reduces the Rate of Posterior Wall Injuries in Central Venous Catheterization: A Simulation Study - Watanabe, Kunitaro (Biomed Res Int, 2018)
The short-axis out-of-plane approach (SAX-OOP) is commonly used in ultrasound-guided internal jugular vein catheterization. However, this approach has a risk of posterior vein wall injuries. The authors hypothesized that a shallow angle of approach may reduce the rate of posterior wall injuries compared with the conventional steep angle approach. The present study aimed to evaluate whether a difference in the angle of approach of the needle affects the rate of posterior wall injuries. The present study was a randomized crossover-controlled trial involving 40 medical residents, conducted in the clinical training center at a hospital with a residency program. The primary outcome measure was the rate of posterior vessel wall injuries. Subjects received a didactic lecture during which the instructors taught three SAX-OOP techniques including the conventional free-hand method (procedure C), a needle navigation system (procedure N), and a shallow puncture angle using a guidance system (procedure S). Participants were trained in these approaches under supervision and each technique tested in a simulation environment. Thirty-four of 40 residents had no previous experience with central venous catheterization and were included in the final analysis. The rate of posterior vessel wall injuries in procedure S (9%) was significantly lower than using the other approaches (procedure C, 53%; procedure N, 41%). In conclusion, a shallow angle of approach using the SAX-OOP technique resulted in significantly fewer posterior vein wall injuries in central venous catheterization compared with steep angle techniques.